(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
Mixed ligand (diphenic/ adipic as primary Ligand and quinoline / 8 - hydroxyquinoline as secondary) transition metal complexes of Cobalt (II), Cupper (II), Rhodium (III) and Platinum (IV) ions were synthesized and characterized. Their antibacterial activities against ten bacteria had been evaluated by the disc diffusion method,whilst their antifungal activities against two fungi had been also evaluated by the same method. Minimum inhibitory concentrations (MIC) had been evaluated against six bacteria. The MIC of the complexes against Shigella dysenteriae, Samonella typhi, Streptococcus-β-haemolyticus and Bacillus megaterium were 32 μg/ml; whilst Escherichia coli and Samonella typhi-A the MIC of Co (II) and Pt (IV) were 32μg/ml and those of Cu(II) and Rh(III) complexes were 64 μg/ml. It was found that Cobalt (II), Cupper (II) & Rhodium (III) complexes had pronounced antibacterial and antifungal activities. Platinum (IV) complex had moderate antibacterial and antifungal activity. These values indicate that these are active compounds. Key words: Mixed Ligand; Transition metal; Antimicrobial Activity; Antifungal Activity Minimum Inhibitory Concentrations (MIC) DOI: http://dx.doi.org/10.3329/bjsir.v46i3.9044 BJSIR 2011; 46(3): 365-368